Fenomena Endorsement terhadap Etika Bisnis Islam - Hidayanti, Nur Fitri; Rahmat, Rahmat; Nabila, Aprilian (Journal of Sharia Economy and Islamic Tourism, 2024)
Abstract: This research aims to analyze the phenomenon of endorsement in the context of Islamic business ethics using a descriptive qualitative method. Through interviews and observations with consumers, the findings reveal that respondents agree that endorsements are effective in increasing sales. However, respondents feel that this practice is not fully aligned with Sharia principles. Some influencers tend to downplay the shortcomings of products, which can pose a risk of deception and contradict the value of honesty in Islam. This study recommends that business practitioners and influencers pay attention to ethical principles, such as transparency and social responsibility, to ensure that endorsements are not only economically beneficial but also in line with Islamic values. It is hoped that the results of this research will provide insights for the industry on the importance of Islamic business ethics in endorsement practices.Abstrak: penelitian ini bertujuan untuk menganalisis fenomena endorsement dalam konteks etika bisnis Islam dengan menggunakan metode kualitatif deskriptif. Melalui wawancara dan observasi terhadap konsumen, hasil penelitian ditemukan bahwa responden setuju bahwa endorsement efektif dalam meningkatkan penjualan. Namun, responden merasa praktik ini belum sepenuhnya sesuai dengan prinsip-prinsip syariah. Beberapa influencer cenderung menutupi kekurangan produk, yang dapat menimbulkan risiko penipuan dan bertentangan dengan nilai kejujuran dalam Islam. Penelitian ini merekomendasikan agar pelaku bisnis dan influencer memperhatikan prinsip etika, seperti transparansi dan tanggung jawab sosial, untuk memastikan bahwa endorsement tidak hanya menguntungkan secara ekonomi tetapi juga sejalan dengan nilai-nilai Islam. Dari hasil penelitian ini diharapkan dapat memberikan wawasan bagi industri tentang pentingnya etika bisnis Islam dalam praktik endorsement.